Exploring Factors Affecting Teachers’ Competence in Digital Assessment Technologies - Amini, Shokoofeh (Assessment and Practice in Educational Sciences, 2023)
This study aims to explore the individual, institutional, and systemic factors influencing teachers’ competence in using digital assessment technologies within the context of Tehran’s educational system. A qualitative research design was adopted, employing semi-structured interviews to gain in-depth insights into teachers’ lived experiences and perspectives. Sixteen in-service teachers from various public and private schools in Tehran were purposefully selected to ensure diversity in teaching backgrounds and technological exposure. Interviews continued until theoretical saturation was achieved. All interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis with the support of NVivo software. Open, axial, and selective coding procedures were employed to identify recurrent patterns and thematic categories related to digital assessment competence. Three overarching themes were identified: individual-level determinants, institutional and infrastructural factors, and systemic and policy-level influences. Subthemes included technological self-efficacy, digital literacy, time management, language barriers, access to infrastructure, professional development quality, administrative support, and policy clarity. Teachers emphasized that while personal motivation and peer collaboration facilitated competence, barriers such as lack of time, inadequate training, unclear policies, and inequitable access significantly impeded effective use of digital assessment tools. Language limitations and platform usability were particularly salient in the Iranian context. Teachers’ competence in digital assessment technologies is shaped by a complex interplay of personal attributes, institutional environments, and broader educational policies. Supporting competence development requires more than technical training—it necessitates systemic alignment, localized resources, and sustained professional support. Addressing these factors can contribute to more equitable, effective, and future-ready assessment practices in digitally evolving educational settings.